Burnout Among Accounting Teachers: The Ethnographic Study in Indonesian Professional Teachers - Syah, Muhammad Fahmi Johan; Harsono; Darmastuti, Mahardika (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to explore the burnout among Indonesian accounting professional certified teachers and to explore how they try to cope with burnout conditions. The study is ethnographic by conducting observations and interviews among certified teachers. The participants are six teachers in Muhammadiyah 1 Karanganyar Senior High School (SMA). The triangulation procedure is conducted regarding the validity of the data, while the data analysis technique consists of data collections, data display, data reduction, and interpretation. The study finds that the certified professional teachers suffer burnout shown by the exhaustion because of teaching hours load, which is they should teach 24 teaching hours in a week. Furthermore, besides it, they must make administrative tasks such as a lesson plan, a semester program, and many others. As a result, the way of teaching in those teachers are likely not expected as a professional teacher. They tend to give assignments to their teachers to have “break” and let the students study by themselves. The striking feature is the age of the teacher that nearly in a retired age shows better the teaching process than the younger teachers even though with some deficiencies. However, they try to solve this condition by being calm, make the relaxed teaching atmosphere, and the most striking feature is the support from their family is reducing their burnout.